The Influence of Financial Literacy and Financial Inclusion on the Performance of MSMEs in the Culinary Sector in West District - Mike Kusuma Dewi; Dinda Nurazizah; Laynita Sari; Gina Septiana; Lisa Amelia (JURNAL COMPUTECH & BISNIS, 2026)
This study examines the partial impacts of financial literacy and financial inclusion on the performance of culinary micro, small, and medium enterprises in the West Padang District. A quantitative research methodology was employed, with data collected through standardized questionnaires. The population comprised 1,922 culinary MSMEs in West Padang District, from which a sample of 95 respondents was selected using the Yamane formula. The data were analyzed via multiple linear regression in SPSS version 26. The statistics demonstrate that financial literacy substantially affects MSME performance, while financial inclusion does not. The results demonstrate that improving financial literacy among MSME participants is crucial for improved business performance, especially profitability. The study emphasizes the importance of improving financial literacy to enable more effective financial decision-making and encourage optimal use of financial services.